MAKNA KARYA SENI MENURUT CLIVE BELL - Ambrosius Markus Loho (JPKS (Jurnal Pendidikan dan Kajian Seni), 2022)
The search of meaning of a work of art is not separated from the constituent element. The work of an art cannot only be enjoyed as a result that already exists and be limited in what appears in front of a subject, each subject has its own perspective. Thus, the beauty of the meaning of the work of art that exists in front of the subject depends on the way of view of the subject. So from that, every work of art is not by itself beautiful and meaningful because it depends on the subject found that would give justification to do it. The work of art becomes meaningful, when the subject found the aesthetic qualities in the work of art itself. In order that, this work of writing will elaborate on the meaning of the work of art for the sake of finding the form of meaning of the work of art. The writing work will focus on the thought of Clive Bell on the form of meaning (significant form).  With a focus on the theory and thinking, the writer will identify the work of art that is meaningful, which starts from the aesthetic qualities of the work of art. For Clive Bell, the meaning of the work of art refers to the qualities of objects appearing and being discovered by the subject. That is the meaningful form of the work of art.keywords: work of art, the meaning of a work of art, meaningful, form, aesthetic, quality.